PERJANJIAN KERJASAMA DI BIDANG JASA ANTARA HOTEL PATRA BALI DENGAN BIRO PERJALANAN WISATA (BPW) PT. SERUM TRANSPORT - Novira Hadi Jayanti, Kadek; Oka Parwata, A. A. Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
The purpose of this paper are to determine the scope of the agreement Patrahotel with a travel agency PT. Seruni Transport and to find remedies that can bedone in the event of default in the agreement between the PT. Patra Hotel withSeruni Transport.The method used is an empirical method that is in fact the approach in whichthe conduct of field research with the fact or facts that are applicable to the issuesraised and how the law operates in society.The results obtained from these problems is the scope of the cooperationagreement between the PT. Patra hotel with PT. Seruni Transport that the timing ofpayments, cancellation of the reservation, the rental price and in the event of defaultbetween the hotel Patra with PT. Transport Seruni the solution is to focus onsupporting the family (non-litigation).
Keywords: Agreement, Default, Non-litigation